The vertical profile of the refraction coefficient for microwave radiation in the troposphere and its variability. Issue 1 (July 2021) - Kuznetsov, A; Seroukhova, O; Simakina, T; Kryukova, S
Abstract: On the basis of data from 8 aerological stations: St. Petersburg, Tallinn, Sukhinichi, Bologoye, Velikiye Luki, Smolensk, Ryazan and Dolgoprudny, the variability of the refractive index vertical profile in the troposphere is shown. It is noted that the presence in the troposphere of inversions of the altitudinal temperature profile and narrow zones with increased and decreased water vapor content leads to sharp changes in the index refractive index gradient and determines the type of radio wave refraction.